Wedangan Omah Lawas Sragen Consumer Decision Analysis in Terms of Instagrammable Places, Product Innovation and Online Promotion through Social Media - Anditya, Rizya; Suwandi, Joko (Universitas Muhammadiyah Surakarta, 2023)
This study aims to describe the analysis of consumer decisions Wedangan Omah Lawas in terms of instagrammable place, product innovation and online promotion through social media. The research method used is qualitative with case study design. Research Data were collected from four consumers who visited Wedangan Omah Lawas. Data collection techniques used in the form of observation, interviews and documentation. Data analysis techniques using interactive models according to Milles & Huberman with the steps of data reduction, data display, conclusion drawing/ verification. While the validity of the data using triangulation techniques. The results of this study are; the decision of consumers to visit Wedangan Omah Lawas is based on instagrammable places that present different photo spots from other places and focus on ancient themes, product innovation by developing food menus and Wedangan Omah Lawas provides several special menus such as Monday and Tuesday offers sego bancaan menus, on Wednesday offers sego jangan lodeh menus, on Thursday offers lontong sayur menus and on, Sunday offers Sego sambel cumi menu and online promotion through social media by uploading photos or videos accompanied by interesting and informative captions.